PENYALAHGUNAAN TEKNOLOGI DIGITAL DALAM TINDAK PIDANA PENCEMARAN NAMA BAIK DALAM PERSPEKTIF HUKUM - Anggraini, latifah Puri; Zubaedah, Rahmi (Jurnal Hukum Positum, 2024)
This study aims to analyse the rehabilitation efforts that can be undertaken by victims of defamation in cyberspace and to examine the countermeasures implemented by law enforcement authorities. The research employs a normative juridical approach by reviewing statutory regulations, legal literature, and case studies related to criminal acts of defamation through social media. The results indicate that the misuse of digital technology has expanded the scope of defamation, causing significant psychological and social impacts on victims. In law enforcement, authorities face challenges such as difficulties in gathering evidence and tracing perpetrators, thus requiring preventive, repressive, and rehabilitative strategies. Preventive efforts are carried out through public education and improving digital literacy, while repressive measures are taken through criminal proceedings against offenders. Meanwhile, rehabilitative efforts focus on restoring the victim’s reputation through the removal of harmful content, public clarification, and the provision of legal protection. In conclusion, addressing defamation in cyberspace requires synergy between law enforcement, enhanced digital awareness, and effective victim recovery mechanisms to achieve justice and protect individual dignity in the digital era.